2017
DOI: 10.4049/jimmunol.1600594
|View full text |Cite
|
Sign up to set email alerts
|

IL-26 Confers Proinflammatory Properties to Extracellular DNA

Abstract: In physiological conditions, self-DNA released by dying cells is not detected by intracellular DNA sensors. In chronic inflammatory disorders, unabated inflammation has been associated with a break in innate immune tolerance to self-DNA. However, extracellular DNA has to complex with DNA-binding molecules to gain access to intracellular DNA sensors. IL-26 is a member of the IL-10 cytokine family, overexpressed in numerous chronic inflammatory diseases, in which biological activity remains unclear. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 72 publications
2
90
2
Order By: Relevance
“…Moreover, we show that expression of the hypomorphic HAQ variant of STING dramatically reduces S. pneumoniae-induced type I IFN responses, but that it appears to have no major influence on the susceptibility of nonvaccinated individuals toward pneumococcal pneumonia or on disease severity. We speculate that the divergent effect of type I IFN versus STING deficiencies on pneumococcal infections can be explained by the capacity of cGAS/STING to also regulate the production of other mediators in addition to type I IFNs (53,54). Indeed, STING-dependent signaling has been shown to activate various transcription factors, such as IRF3, NF-B, and STAT6 (21,53).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we show that expression of the hypomorphic HAQ variant of STING dramatically reduces S. pneumoniae-induced type I IFN responses, but that it appears to have no major influence on the susceptibility of nonvaccinated individuals toward pneumococcal pneumonia or on disease severity. We speculate that the divergent effect of type I IFN versus STING deficiencies on pneumococcal infections can be explained by the capacity of cGAS/STING to also regulate the production of other mediators in addition to type I IFNs (53,54). Indeed, STING-dependent signaling has been shown to activate various transcription factors, such as IRF3, NF-B, and STAT6 (21,53).…”
Section: Discussionmentioning
confidence: 99%
“…While immunofluorescence staining of skin sections of hIL-26Tg mice indicated that IL-26 was produced by CD4-positive cells as well as other cell types, the cells involved may differ in the IMQ-induced psoriasis model from psoriasis patients (Figure 3b, 3d). In addition to Th17 cells, other IL-26eproducing cells have been identified recently (Che et al, 2014(Che et al, , 2017Corvaisier et al, 2012;Poli et al, 2017). In the skin lesions of psoriatic patients, IL-17 is produced not only from CD4 þ T cells, but also from CD8 þ T cells and gd T cells (Golden et al, 2013;Matos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the re-entry process of self-DNA in host cells is a biological feature that clearly differentiates NETs and mononucleosomes. (This process has been well reviewed by Poli et al, 2017) Nucleic acids appear to be the main source of DAMPs, and stimulate Pattern Recognition Receptors (PRR) to induce inflammation (Elkon et al, 2019). The location of nucleic acid sensing receptors can be conveniently divided into endosomal and cytosolic.…”
Section: Nuclear Dnamentioning
confidence: 99%